A waterborne acrylic polyurethane finish and a method of making the same

CN122080760BActive Publication Date: 2026-10-23江苏德威涂料有限公司
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202610520443.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-04-20
Publication Date
2026-10-23
Estimated Expiration
2046-04-20

AI Technical Summary

Technical Problem

[0005]活化期与固化速度的权衡:对于高性能的双组分水性丙烯酸-聚氨酯面漆,其综合性能优于单组分体系,但存在活化期(适用期)与干燥速度难以兼顾的固有矛盾

Benefits of technology

1.综合性能优异:通过高低分子量复配树脂体系,成功解决了快干性与高丰满度、高交联密度之间的矛盾,实现了漆膜表干快(≤20分钟)、实干迅速(≤2.5小时),同时具有高光泽(60°光泽≥90)和优异的机械性能。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The application discloses a kind of water-based acrylic polyurethane finish and preparation method thereof, including component A and component B;The A component includes the following components: high low molecular weight compound hydroxyl acrylic resin 35-50 parts, modified nanometer hybrid material 2-5 parts, composite functional filler 15-25 parts, latent catalyst 1-3 parts, auxiliary agent 3-6 parts and deionized water 20-30 parts;The B component is crosslinking agent;The modified nanometer hybrid material is the hybrid material that in-situ compounding is formed by the surface modification of nanometer boron nitride with silane coupling agent and graphene oxide;The latent catalyst is the metal complex that metal compound is pre-complexed with complexing agent;Through high low molecular weight compound resin system, the contradiction between quick drying and high fullness, high crosslinking density is successfully solved, realizes that paint film surface is dry fast, real dry quickly, simultaneously has high gloss and excellent mechanical property.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of coating technology, specifically referring to a water-based acrylic polyurethane topcoat and its preparation method. Background Technology

[0002] With increasingly stringent global environmental regulations and growing public awareness of ecological and environmental issues, the coatings industry is accelerating its development towards low volatile organic compound (VOC) emissions, low toxicity, and energy conservation and environmental protection. Water-based coatings, using water as the dispersion medium, fundamentally reduce the use of organic solvents and have become one of the mainstream products replacing traditional solvent-based coatings. Among them, water-based acrylic polyurethane topcoats are widely used in industrial protection and decoration fields due to their excellent weather resistance, gloss and color retention, good adhesion, and relatively economical cost.

[0003] However, existing waterborne acrylic polyurethane topcoats still exhibit some technical bottlenecks when facing more demanding application requirements, mainly in the following aspects: The contradiction between drying speed and overall performance: To achieve rapid drying and meet the demands of efficient application, current technologies often employ methods that increase the glass transition temperature (Tg) of the resin. However, while high-Tg resins can achieve fast surface drying and good initial anti-tack properties, they often result in poor leveling, low gloss, and poor flexibility of the paint film. Furthermore, due to restricted molecular chain movement, the reactivity with the crosslinking agent is reduced, making it difficult to form a high-density crosslinking network, ultimately affecting the long-term protective performance of the paint film. Conversely, while low-Tg or low-molecular-weight resins can achieve good leveling and crosslinking density, the initial drying speed of the paint film is slow, it is prone to dust accumulation, and its application performance is poor in low-temperature and high-humidity environments.

[0004] The Dispersion Challenges of Functional Reinforcers: To improve the mechanical strength, corrosion resistance, and weather resistance of coating films, existing technologies attempt to introduce various nanomaterials (such as nano-silica, nano-zinc oxide, carbon nanotubes, etc.) or flake fillers (such as mica powder, glass flakes) into coating systems. However, these nano- or micron-sized particles, due to their high surface energy and large specific surface area, are prone to agglomeration in aqueous systems. This not only fails to achieve their intended function but may also become structural defects in the coating film, leading to decreased gloss, increased pinholes, and even premature failure. Achieving long-term, stable, and uniform dispersion of functional fillers in the resin matrix is ​​a major technical challenge in this field.

[0005] The trade-off between activation period and curing speed: For high-performance two-component waterborne acrylic-polyurethane topcoats, their overall performance is superior to that of single-component systems, but there is an inherent contradiction between balancing activation period (potential life) and drying speed. To achieve rapid curing, highly efficient catalysts such as organotin compounds are usually added, but this drastically shortens the coating's activation period from tens of minutes to less than an hour, causing significant inconvenience and material waste during on-site application. Without a catalyst or using a low-activity catalyst, the curing reaction is slow, especially at low temperatures, resulting in low coating efficiency. How to ensure a relatively long activation period (e.g., 2-4 hours) while achieving rapid drying of the coating film (e.g., complete drying within 2.5 hours) is a problem that current technology urgently needs to solve.

[0006] Limitations and High Energy Consumption of Single-Component Systems: Single-component waterborne acrylic polyurethane topcoats (containing hydroxyl acrylic resin and amino resin) are easy to apply, but typically require high baking temperatures (≥140℃) to achieve sufficient cross-linking and curing to obtain ideal chemical resistance and hardness. This not only consumes a large amount of energy but also limits their application on heat-sensitive substrates. Furthermore, existing single-component systems generally fall short of the water resistance and corrosion resistance levels of two-component systems.

[0007] Single barrier mechanisms have limited efficiency: In existing technologies, whether by adding a single type of sheet-like filler (such as mica powder) or by increasing the crosslinking density of the resin, the barrier structure formed is relatively simple. It has limited effect on extending the penetration path of water, oxygen and corrosive ions (such as chloride ions), making it difficult to achieve long-term and efficient shielding against corrosive media.

[0008] Therefore, developing a high-performance waterborne acrylic polyurethane topcoat that can simultaneously achieve excellent environmental adaptability (such as fast drying), superior physical and mechanical properties, long-lasting corrosion resistance, and a good application window, while solving many of the problems in the existing technologies mentioned above, has significant practical implications and commercial value. Summary of the Invention

[0009] To address the needs and problems mentioned in the background above, the present invention provides a water-based acrylic polyurethane topcoat and its preparation method, thereby at least partially solving the above-mentioned problems.

[0010] According to the technical solution of the present invention, a water-based acrylic polyurethane topcoat is provided, comprising component A and component B; Component A comprises the following components by mass parts: The mixture consists of 35-50 parts of high and low molecular weight compounded hydroxyl acrylic resin, 2-5 parts of modified nano-hybrid materials, 15-25 parts of composite functional filler, 1-3 parts of potential catalyst, 3-6 parts of additives, and 20-30 parts of deionized water. Component B is a crosslinking agent; The high and low molecular weight compounded hydroxy acrylic resin includes high molecular weight hydroxy acrylic resin and low molecular weight hydroxy acrylic resin. The modified nano-hybrid material is a hybrid material formed by in-situ composite of nano-boron nitride modified with silane coupling agent and graphene oxide. The potential catalyst is a metal complex formed by pre-complexing a metal compound with a complexing agent.

[0011] Preferably, the high molecular weight hydroxyl acrylic resin has a number average molecular weight of 50,000-80,000, a glass transition temperature of 40-60℃, and a hydroxyl value of 30-60 mgKOH / g. The low molecular weight hydroxyl acrylic resin has a number average molecular weight of 2000-5000 and a hydroxyl value of 120-160 mgKOH / g; the mass ratio of the high molecular weight hydroxyl acrylic resin to the low molecular weight hydroxyl acrylic resin is (1-2):1.

[0012] Preferably, the modified nano-hybrid material contains hexagonal boron nitride with a sheet diameter of 100-500 nm and a thickness of 10-50 nm. The graphene oxide has a sheet diameter of 1-5 μm and a carbon-to-oxygen ratio of (2-4):1; The mass ratio of the nano-boron nitride to graphene oxide is (5-10):1; The silane coupling agent includes γ-methacryloxypropyltrimethoxysilane.

[0013] Preferably, the metal compound in the potential catalyst includes one or more of organobismuth, organozinc, and organozirconium. The complexing agent includes one or more of acetylacetone, 2,2'-bipyridine, and ethylenediaminetetraacetic acid; The molar ratio of the metal compound to the complexing agent is 1:(1-3).

[0014] Preferably, the composite functional packing includes micron-sized sheet packing and submicron-sized spherical packing; The micron-sized sheet-like filler includes at least one of sericite, kaolin, or talc, with a particle size of 5-15 μm. The submicron-sized spherical packing is selected from nano-barium sulfate or precipitated barium sulfate, with a particle size of 0.1-1μm; the mass ratio of the micron-sized sheet packing to the submicron-sized spherical packing is (2-3):1.

[0015] Preferably, component B is a hydrophilic modified isocyanate curing agent, which includes hexamethylene diisocyanate trimer or its derivatives; The ratio of component A to component B satisfies the molar ratio of NCO:OH as (1.2-1.5):1.

[0016] Preferably, the topcoat is a single-component system, with component B omitted, and 5-15 parts of methyl etherified amino resin added to component A as a crosslinking agent.

[0017] Preferably, the additives include at least one of wetting and dispersing agents, substrate wetting agents, defoamers, film-forming aids, and rheology modifiers; Component A further includes a neutralizing agent, which includes at least one of N,N-dimethylethanolamine, 2-amino-2-methyl-1-propanol and triethylamine, for adjusting the pH of component A to 7.5-8.5.

[0018] On the other hand, the present invention also provides a method for preparing a water-based acrylic polyurethane topcoat, comprising the following steps: Pre-dispersion of hybrid materials: The prescribed amount of graphene oxide is added to a portion of deionized water and subjected to a first ultrasonic dispersion treatment to obtain a graphene oxide dispersion; under stirring conditions, nano-boron nitride modified with a silane coupling agent is slowly added to the graphene oxide dispersion, and then subjected to a second ultrasonic dispersion treatment to obtain a uniform and stable modified nano-hybrid material slurry. Paint slurry grinding: Mix the high and low molecular weight compounded hydroxy acrylic resin, some additives, composite functional fillers and the remaining deionized water evenly, put them into a sand mill for grinding and dispersion until the slurry fineness is ≤20μm. Paint mixing: In the qualified ground paint slurry, under stirring conditions, slowly add the modified nano-hybrid material slurry, the formula amount of potential catalyst, the remaining additives, and the neutralizer to adjust the pH value to 7.5-8.5, and continue stirring until uniform; Filtration: The mixed paint material is filtered through a filter screen to obtain component A of the topcoat; Packaging: Package component A and component B separately.

[0019] Thirdly, the present invention also provides an application of a waterborne acrylic polyurethane topcoat, which is used in the coating of metal substrates, including surface protection and decoration of engineering machinery, rail transportation, steel structures or automotive parts.

[0020] Beneficial effects: 1. Excellent overall performance: By using a high- and low-molecular-weight compound resin system, the contradiction between fast drying and high fullness and high crosslinking density has been successfully resolved, achieving fast surface drying (≤20 minutes) and rapid hard drying (≤2.5 hours) of the paint film, while also having high gloss (60° gloss ≥90) and excellent mechanical properties.

[0021] 2. Long-lasting corrosion protection: By constructing a unique micron-nano multi-level composite barrier structure, combined with the reinforcing effect of modified nano-hybrid materials, the shielding ability of the paint film against water, oxygen and corrosive media is greatly improved. The salt spray resistance is 2-3 times better than that of conventional water-based acrylic polyurethane topcoats, and the early water stain resistance is excellent.

[0022] 3. Wide application window and broad adaptability: The introduced latent catalyst technology gives the two-component system an activation period of 4-6 hours, greatly facilitating on-site application and ensuring rapid curing after coating. In single-component baking paint systems, the curing temperature can be effectively reduced to 100-110℃, saving energy and expanding the application range.

[0023] 4. Integrated Material Functions: The application of modified nano-boron nitride and graphene oxide hybrid materials not only solves the problem of nanoparticle dispersion, but also endows the paint film with multiple functions such as thermal conductivity, barrier, reinforcement, and wear resistance, realizing the integrated design of material functions.

[0024] 5. Environmental protection and safety: The product uses water as the dispersion medium and has extremely low VOC content, which meets the requirements of current environmental protection regulations. Detailed Implementation

[0025] The technical solutions in the embodiments will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection.

[0026] This invention provides a water-based acrylic polyurethane topcoat, constructing a composite system with multiple synergistic effects. Specifically, this is achieved through a compound resin system, a specific functional filler combination, delayed catalytic crosslinking technology, and a composite barrier structure. The topcoat comprises at least component A and component B, wherein: Component A, by mass parts, includes the following components: The mixture consists of 35-50 parts of high and low molecular weight compounded hydroxyl acrylic resin, 2-5 parts of modified nano-hybrid materials, 15-25 parts of composite functional filler, 1-3 parts of potential catalyst, 3-6 parts of additives, and appropriate amounts of neutralizer and deionized water.

[0027] Component B is a crosslinking agent.

[0028] (I) High and low molecular weight compounded hydroxyl acrylic resins: The high- and low-molecular-weight compounded hydroxyl acrylic resins described in this invention are not simple physical mixtures, but rather carefully designed resin combinations with differentiated functional groups and molecular weight distributions, comprising: The first hydroxyl acrylic resin is a high molecular weight acrylic copolymer with a high glass transition temperature (Tg), a number average molecular weight (Mn) of 50,000-80,000, a glass transition temperature (Tg) of 40-60℃, and a hydroxyl value of 30-60 mgKOH / g.

[0029] Secondary hydroxyl acrylic resin is a low molecular weight, high hydroxyl value acrylic copolymer with a number average molecular weight (Mn) of 2000-5000 and a hydroxyl value of 120-160 mgKOH / g.

[0030] The mass ratio of the first resin to the second resin is (1-2):1.

[0031] Technical principles and functions: This invention cleverly combines these two resins. In the initial stages of coating, the first resin segments, with their high Tg and high molecular weight, rapidly entangle and accumulate on the paint film surface as moisture evaporates, forming a physical framework structure. This imparts excellent initial drying speed and anti-tack properties to the paint film, solving the problem of slow drying typically found in high crosslinking density systems. Simultaneously, the second resin, with its smaller molecular weight and higher hydroxyl value, exhibits good flowability, effectively penetrating the gaps in the framework constructed by the first resin and carrying abundant reactive hydroxyl groups (-OH).

[0032] In the later stages of film formation, whether reacting with the added isocyanate curing agent (component B) or with the amino resin within the system (in a single-component baking paint system), the second resin provides ample crosslinking points, participating in the reaction together with the hydroxyl groups on the surface of the first resin to form a highly crosslinked, uniform, and dense three-dimensional chemical network. This dual mechanism of physical framework locking and chemical network filling allows the final paint film to achieve excellent fullness, gloss, and mechanical properties while possessing fast drying properties.

[0033] (II) Modified nano-hybrid materials: To address the issue of nanoparticle agglomeration and to endow paint films with multiple functions, this invention presents and introduces a specific modified nano-hybrid material. This material is formed by in-situ composite of nano-boron nitride modified with a silane coupling agent and graphene oxide.

[0034] The boron nitride nanoparticles are hexagonal boron nitride (h-BN) with a sheet diameter of 100-500 nm and a thickness of 10-50 nm; the graphene oxide has a sheet diameter of 1-5 μm and a carbon-to-oxygen ratio of (2-4):1.

[0035] The mass ratio of the nano-boron nitride to graphene oxide is (5-10):1.

[0036] During preparation, graphene oxide is first ultrasonically dispersed in water, and then boron nitride nanoparticles modified with a silane coupling agent (such as γ-methacryloyloxypropyltrimethoxysilane, KH-570) are added. Through ultrasonic and mechanical stirring, the boron nitride nanoparticles are uniformly loaded on the surface or between layers of graphene oxide sheets through π-π stacking and hydrogen bonding, forming a unique hybrid structure of two-dimensional material loaded with zero-dimensional / one-dimensional particles.

[0037] Technical principles and functions: Synergistic dispersion mechanism: Graphene oxide itself contains oxygen-containing functional groups, giving it a certain degree of dispersibility in water and resin. Using it as a carrier guides the orderly arrangement of boron nitride nanoparticles on its surface, effectively preventing the self-aggregation of high surface energy boron nitride nanoparticles. Simultaneously, the layered structure of graphene oxide also provides a huge surface area for loading boron nitride nanoparticles.

[0038] Multiple feature enhancements: Nano boron nitride: Its high thermal conductivity helps to quickly conduct and disperse the heat generated by local heating of the paint film (such as welding, direct sunlight), avoiding paint film cracking caused by thermal stress concentration; its inherent lubricity and high hardness help to improve the scratch resistance and wear resistance of the paint film; its sheet-like structure itself also has a physical barrier effect.

[0039] Graphene oxide: Due to its extremely high aspect ratio, it forms a labyrinth effect in the paint film, greatly extending the time for water, oxygen, and corrosive ions (such as Cl-) to pass through. - The penetration pathway of graphene oxide significantly improves the barrier properties and salt spray corrosion resistance of the coating film. Simultaneously, the functional groups on the surface of graphene oxide can form hydrogen bonds or chemical bonds with the resin matrix, enhancing interfacial adhesion and thus improving the toughness and impact resistance of the coating film.

[0040] The combination of the two achieves a triple function of heat conduction, reinforcement, and barrier that is difficult to achieve with a single material.

[0041] (III) Potential Catalysts: To overcome the contradiction between the activation period and curing speed of two-component coatings and to reduce the curing temperature of single-component baking paints, this invention introduces a metal complex latent catalyst. The latent catalyst is formed by pre-complexing a metal compound with a complexing agent.

[0042] The metal compound is selected from one or more of organobismuth, organozinc, or organozirconium.

[0043] The complexing agent is selected from one or more of acetylacetone, 2,2'-bipyridine, and ethylenediaminetetraacetic acid.

[0044] The molar ratio of the metal compound to the complexing agent is 1:(1-3).

[0045] Technical principles and functions: Application in two-component systems: In the initial stage of coating mixing (component A and component B are mixed), the catalytic activity of metal ions is temporarily inhibited due to the blocking effect of the complexing agent, preventing effective catalysis of the reaction between hydroxyl groups (-OH) and isocyanate groups (-NCO). Therefore, the coating system exhibits excellent storage stability and an activation period of 4-6 hours. When the coating is applied to the substrate, the system environment (e.g., pH changes, polarity changes) changes with the evaporation of moisture and a small amount of co-solvent, disrupting the complexation equilibrium and allowing the metal ions to be released in situ and slowly. The released highly active metal ions rapidly catalyze the reaction between -NCO and -OH, thereby achieving ultra-fast curing of the paint film (e.g., surface dry ≤ 15 minutes, hard dry ≤ 2.5 hours).

[0046] Applications in single-component baking paint systems: In water-based acrylic-amino baking paints, this latent catalyst remains dormant at room temperature, not affecting the storage stability of the coating. When the paint film enters the baking stage, and the temperature rises to 100-110℃, the complex dissociates upon heating, releasing metal ions. These metal ions, acting as Lewis acid catalysts, effectively reduce the activation energy of the etherification crosslinking reaction between amino resins and hydroxyl acrylic resins, thereby lowering the traditional curing temperature of over 140℃ by 20-30℃, achieving energy saving and consumption reduction, and broadening its application range.

[0047] (iv) Composite functional packing and three-dimensional multi-level packing barrier structure: To further enhance the shielding effect of the coating film, this invention constructs a three-dimensional multi-level filler barrier structure ranging from micrometers to nanometers. The composite functional filler includes: Micron-sized sheet-like fillers, selected from at least one of sericite, kaolin, or talc, with a particle size of 5-15 μm.

[0048] Submicron-sized spherical fillers, selected from nano-barium sulfate or precipitated barium sulfate, with a particle size of 0.1-1μm.

[0049] The mass ratio of the micron-sized sheet packing to the submicron-sized spherical packing is (2-3):1.

[0050] Furthermore, this composite functional filler works in conjunction with the aforementioned modified nano-hybrid material.

[0051] Technical principles and functions: During the paint film drying process, micron-sized sheet-like fillers (such as sericite) tend to align parallel to the substrate surface, forming the first macroscopic physical barrier, effectively preventing the direct intrusion of external corrosive media. However, microscopic gaps inevitably exist between these micron-sized sheets. At this point, submicron-sized spherical fillers (such as nano-barium sulfate) can fill these gaps, playing a role in dense packing and reducing porosity. More importantly, the nanoscale modified nano-hybrid material (i.e., graphene oxide loaded with boron nitride) in this invention can further fill the even smaller gaps formed by the submicron fillers and tightly bond with the resin matrix through chemical bonds or hydrogen bonds. Thus, a three-dimensional multi-level filler barrier structure is formed, consisting of a micron-sized sheet-like filler (such as sericite) as the basic barrier layer, a submicron-sized spherical filler as the gap-filling layer, and a nano-hybrid material as an ultrafine gap-filling and reinforcing layer. This structure maximally distorts and extends the diffusion channels of corrosive media, maximizing the barrier efficiency of the paint film and significantly enhancing the early water stain resistance and long-term salt spray resistance of the paint film.

[0052] (V) Additives and Neutralizing Agents: The additives mentioned are conventional coating additives used in the art, including but not limited to: wetting and dispersing agents (such as BYK-190, TegoDispers755W), substrate wetting agents (such as BYK-346, TegoWet270), defoamers (such as BYK-024, TegoFoamex810), film-forming aids (such as dipropylene glycol butyl ether, tripropylene glycol butyl ether), and rheology modifiers (such as polyurethane thickeners). The dosage of each additive can be adjusted within the conventional range in the art according to actual needs.

[0053] The neutralizing agent is used to adjust the pH of component A to a weakly alkaline state (pH 7.5-8.5) to facilitate the stability of the resin's water solubility or water dispersibility. It can be selected from one or more of N,N-dimethylethanolamine (DMEA), 2-amino-2-methyl-1-propanol (AMP-95), or triethylamine.

[0054] (vi) Crosslinking agent (component B): When the topcoat of this invention is designed as a two-component system, component B is a hydrophilic modified isocyanate curing agent, such as hexamethylene diisocyanate (HDI) trimer or its derivatives, such as Covestro 304, Asahi Kasei TPA-100, etc. Its dosage can be calculated based on the total hydroxyl value of component A, typically with a molar ratio of NCO:OH of (1.2-1.5):1. To reduce its viscosity and improve mixing performance, component B may also contain environmentally friendly solvents such as propylene glycol diacetate for dilution.

[0055] When the topcoat of this invention is designed as a single-component baking paint system, component A must also contain 5-15 parts of methylated amino resin (such as Cymel 303, 325) as a crosslinking agent, and component B is not present.

[0056] This invention also provides a method for preparing the waterborne acrylic polyurethane topcoat, comprising the following steps: Pre-dispersion of hybrid materials: The prescribed amount of graphene oxide is added to a portion of deionized water and subjected to a first ultrasonic dispersion treatment to obtain a graphene oxide dispersion; under stirring conditions, nano-boron nitride modified with a silane coupling agent is slowly added to the graphene oxide dispersion, and then subjected to a second ultrasonic dispersion treatment to obtain a uniform and stable modified nano-hybrid material slurry.

[0057] Paint slurry grinding: Mix the high and low molecular weight compound hydroxy acrylic resin, some additives (including wetting and dispersing agents, some defoamers), composite functional fillers and the remaining deionized water evenly, and put them into a sand mill for grinding and dispersion until the slurry fineness is ≤20μm.

[0058] Paint mixing: In the qualified ground paint slurry, under stirring conditions, slowly add the modified nano-hybrid material slurry, the amount of latent catalyst in the formula, the remaining additives (including substrate wetting agent, remaining defoamer, film-forming aid, rheology aid), and neutralizer to adjust the pH value to 7.5-8.5, and continue to stir at medium speed until uniform.

[0059] Filtration: The prepared paint material is filtered through a 200-mesh or higher mesh filter to obtain component A of the topcoat.

[0060] Packaging: Package component A and component B (crosslinking agent) separately to obtain the finished product.

[0061] It should be noted that, unless otherwise specified, all raw materials used in the following embodiments are commercially available industrial products. Among them: High molecular weight hydroxyl acrylic resin A1: Mn=60000, Tg=50℃, hydroxyl value 45mgKOH / g, solid content 45%; High molecular weight hydroxyl acrylic resin A2: Mn=75000, Tg=58℃, hydroxyl value 35mgKOH / g, solid content 45%; Low molecular weight hydroxyl acrylic resin B1: Mn=3500, hydroxyl value 140mgKOH / g, solid content 80%; Low molecular weight hydroxyl acrylic resin B2: Mn=4500, hydroxyl value 120mgKOH / g, solid content 80%; Nano boron nitride (h-BN): sheet diameter 200-400nm, thickness 20-40nm; Graphene oxide (GO): sheet diameter 2-4 μm, carbon-oxygen ratio 3:1; Sericite: 1250 mesh; Nano-barium sulfate: particle size 0.2-0.5μm; Potential catalyst C1: organobismuth / acetylacetone complex (molar ratio 1:2); Potential catalyst C2: organozinc / 2,2'-bipyridine complex (molar ratio 1:1.5); Hydrophilic modified HDI trimer: NCO content approximately 20%, Bayer 304; Methioninated amino resin: Cymel 303; Additives: BYK-190 (dispersant), BYK-024 (defoamer), BYK-346 (wetting agent), dipropylene glycol butyl ether (film-forming aid), AMP-95 (neutralizer).

[0062] Example 1 (1) Preparation of modified nano-hybrid material slurry: 0.8 parts of graphene oxide were added to 15 parts of deionized water and ultrasonically dispersed for 30 minutes (500W) to obtain a GO dispersion. 4.2 parts of KH-570 modified boron nitride nanoparticles were slowly added under stirring, and ultrasonic dispersion was continued for 20 minutes to obtain a uniform gray-black hybrid material slurry (solid content approximately 25%).

[0063] (2) Grinding of lacquer paste: Mix 20 parts of high molecular weight resin A1, 15 parts of low molecular weight resin B1, 1.5 parts of BYK-190, 0.3 parts of BYK-024, 15 parts of sericite, 5 parts of nano barium sulfate, and 10 parts of deionized water evenly, and then grind them in a sand mill until the fineness is ≤20μm.

[0064] (3) Paint mixing: In the ground paint slurry, slowly add all the hybrid material slurry prepared in (1), add 2 parts of latent catalyst C1, 0.3 parts of BYK-346, 0.2 parts of BYK-024 (added later), and 4 parts of dipropylene glycol butyl ether. Adjust the pH to 8.0 with AMP-95 and stir at medium speed for 30 minutes.

[0065] (4) Filter packaging: Filter through a 200-mesh screen to obtain component A. Component B is a hydrophilic modified HDI trimer (mixed according to NCO:OH = 1.3:1 before use).

[0066] Example 2 Adjust the ratio of high and low molecular weight resins, and follow the same procedure as in Example 1.

[0067] Among them, high molecular weight resin A1: 25 parts; Low molecular weight resin B1: 12 parts; The remaining components and preparation process are the same as in Example 1.

[0068] Example 3 Adjust the amount of modified nano-hybrid material, otherwise remain the same as in Example 1.

[0069] Graphene oxide: 0.5 parts; Modified nano-boron nitride: 2.5 parts; The remaining components and preparation process are the same as in Example 1.

[0070] Example 4 C2 was used instead of C1, and everything else was the same as in Example 1.

[0071] Potential catalyst C2: 2 parts; The remaining components and preparation process are the same as in Example 1.

[0072] Example 5 Adjust the ratio of the composite functional filler, and otherwise follow the same procedure as in Example 1.

[0073] Sericite: 18 parts; Nano barium sulfate: 7 parts; The remaining components and preparation process are the same as in Example 1.

[0074] Example 6 (1) The preparation of the modified nano-hybrid material slurry is the same as in Example 1.

[0075] (2) Grinding of lacquer paste: Mix 22 parts of high molecular weight resin A1, 18 parts of low molecular weight resin B1, 1.5 parts of BYK-190, 0.3 parts of BYK-024, 12 parts of sericite, 6 parts of nano barium sulfate, and 12 parts of deionized water evenly and grind until the fineness is ≤20μm.

[0076] (3) Paint mixing: In the ground paint slurry, slowly add all the hybrid material slurry prepared in (1), add 8 parts of methyl etherified amino resin, 2 parts of latent catalyst C1, 0.3 parts of BYK-346, 0.2 parts of BYK-024, and 5 parts of dipropylene glycol butyl ether. Adjust the pH to 8.0 with AMP-95 and stir at medium speed for 30 minutes.

[0077] (4) Filter packaging: The single-component topcoat was obtained by filtering through a 200-mesh filter.

[0078] Example 7 The resin type was changed, and everything else remained the same as in Example 6.

[0079] High molecular weight resin A2: 20 parts; Low molecular weight resin B2: 18 parts; The remaining components and preparation process are the same as in Example 6.

[0080] Example 8 Adjust the dosage of each component in the formulation and examine the performance under high filler content.

[0081] High molecular weight resin A1: 20 parts; Low molecular weight resin B1: 15 parts; Sericite: 18 parts; Nano barium sulfate: 7 parts; Hybrid material (0.8 parts GO + 4.2 parts BN); The remaining components and preparation process are the same as in Example 1.

[0082] Example 9 Adjust the amount of potential catalyst.

[0083] Potential catalyst C1: 1 part; The remaining components and preparation process are the same as in Example 1.

[0084] Example 10 Adjust the amount of potential catalyst.

[0085] Potential catalyst C1: 3 parts; The remaining components and preparation process are the same as in Example 1.

[0086] Comparative Example 1 Formula adjustments: High molecular weight resin A1: 35 parts; Low molecular weight resin B1: 0 parts; To maintain solids content, add 5 parts deionized water; The remaining components and preparation process are the same as in Example 1.

[0087] Comparative Example 2 Formula adjustments: High molecular weight resin A1: 0 parts; Low molecular weight resin B1: 35 parts (equivalent to 28 parts dry resin based on solid content, water content needs to be adjusted); The remaining components and preparation process are the same as in Example 1.

[0088] Comparative Example 3 Formula adjustments: Eliminate modified nano-hybrid material slurry; Add 15 parts of deionized water; The remaining components and preparation process are the same as in Example 1.

[0089] Comparative Example 4 Formula adjustments: Eliminate modified nano-hybrid material slurry; Four parts of unmodified nano boron nitride (without hybridization with GO) were added directly. Add 11 parts deionized water; The remaining components and preparation process are the same as in Example 1.

[0090] Comparative Example 5 Formula adjustments: Remove potential catalyst C1; The remaining components and preparation process are the same as in Example 1.

[0091] Comparative Example 6 Formula adjustments: Remove potential catalyst C1; Add 0.5 parts of dibutyltin dilaurate (DBTDL, a common catalyst); The remaining components and preparation process are the same as in Example 1.

[0092] Comparative Example 7 Formula adjustments: Eliminate sericite and nano-barium sulfate; Add 15 parts of deionized water; The remaining components and preparation process are the same as in Example 1.

[0093] The performance of the waterborne acrylic polyurethane topcoats prepared in the examples and comparative examples was tested according to the standards and methods in Table 1 below: Table 1 Note: When testing the two-component system, components A and B are mixed evenly at NCO:OH = 1.3:1 before preparing the board; when testing the single-component system (Examples 6 and 7), no curing agent is added, and the system is cured under baking conditions (110℃ / 20min) before testing.

[0094] The data obtained from the above tests are shown in Tables 2 and 3 below: Table 2 Performance test data of the embodiment Note: i. Water resistance is the longest time during which the paint film does not bubble or peel off; ii. Salt spray resistance is the time during which the etched area erodes ≤2mm on one side; iii. Storage stability: Excellent indicates no sedimentation or skinning after heat storage, and viscosity change <10%; Good indicates slight sedimentation, which can be re-stirred.

[0095] In the list of examples, 1-10 represent Examples 1-10, respectively. Examples 6 and 7 are single-component systems that are cured by baking at 110°C for 20 minutes. The surface drying / complete drying time is the baking condition.

[0096] Table 3 Comparative Performance Test Data Note: i. Comparative Example 4 shows poor storage stability, indicating significant sedimentation and hardening at the bottom of the boron nitride nanoparticles; ii. Comparative Example 6 shows poor storage stability, indicating gelation 1 hour after mixing. Examples 1-7 in the comparative example column represent Comparative Examples 1-7, respectively.

[0097] As can be seen from the comparison of data in Table 1-2: Comparative Example 1 (high molecular weight resin only): The surface drying time was only 10 minutes, showing excellent fast drying properties, but the actual drying time was as long as 4.5 hours, the gloss was only 82, and the adhesion dropped to grade 1. This is because although high molecular weight resin can dry physically quickly, it lacks sufficient hydroxyl groups to participate in chemical cross-linking, resulting in insufficient cross-linking density, which affects the fullness and final hardness of the paint film.

[0098] Comparative Example 2 (low molecular weight resin only): gloss up to 95, adhesion grade 0, complete drying time 6.0 h, but surface drying time as long as 45 min. Low molecular weight resin has good flowability and sufficient cross-linking, but its initial physical drying is extremely slow and it is easily contaminated with dust.

[0099] Example 1 (Compound System): Surface drying time 15 min, complete drying time 2.0 h, gloss 93, adhesion grade 0, achieving a balance between fast drying and high fullness. This indicates that the high molecular weight resin provides the initial physical framework, while the low molecular weight, high hydroxyl value resin fills the network and increases the crosslinking density; the synergistic effect of the two is significant.

[0100] Comparative Example 3 (without hybrid material): The pencil hardness decreased to HB, the impact resistance was only 30 cm, and the salt spray resistance was 240 h, which is significantly lower than the 600 h of Example 1. This indicates that the hybrid material makes a significant contribution to the coating film reinforcement and corrosion resistance.

[0101] Comparative Example 4 (Ordinary unmodified nano-boron nitride): Poor storage stability, significant sedimentation of nanoparticles; gloss reduced to 88, adhesion grade 1, and salt spray resistance only 280h. This indicates that unmodified nano-boron nitride is extremely prone to agglomeration in aqueous systems, failing to provide reinforcement and instead becoming a defect in the paint film.

[0102] Example 1 (Hybrid Material): Excellent storage stability, pencil hardness 2H, impact resistance 50cm, and salt spray resistance 600h. Graphene oxide serves as a carrier to guide the uniform dispersion of boron nitride nanoparticles, forming a two-dimensional material-loaded nanoparticle structure, solving the dispersion problem and endowing the paint film with triple functions of thermal conductivity, reinforcement, and barrier properties.

[0103] Comparative Example 5 (without catalyst): The activation period was as long as 6.5 hours, but the surface drying time was 35 minutes and the actual drying time was 5.0 hours, indicating an extremely slow drying speed. Without a catalyst, the reaction activity between hydroxyl groups and isocyanates was low, which could not meet the requirements for high-efficiency construction.

[0104] Comparative Example 6 (common catalyst DBTDL): Surface drying time 12 min, actual drying time 1.5 h, fast drying speed, but activation period only 1.0 h, poor storage stability (gels 1 hour after mixing). Although common catalysts can accelerate curing, they significantly shorten the activation period, making on-site construction difficult.

[0105] Example 1 (Potential Catalyst C1): Surface drying time was 15 min, and actual drying time was 2.0 h, demonstrating excellent drying speed, while the activation period was as long as 5.0 h. The metal complex was in an inactive state in the initial stage of mixing, ensuring a long activation period; after film formation, with the evaporation of water and changes in pH, the catalyst was released in situ, accelerating the crosslinking reaction, thus achieving an ideal balance between activation period and drying speed.

[0106] Comparative Example 7 (without composite functional filler): Water resistance 96h, salt spray resistance 240h, significantly lower than >240h and 600h in Example 1. This indicates that the multi-level barrier structure of micron-scale sheets and nanospheres constructed from sericite and nano-barium sulfate can effectively extend the penetration path of corrosive media.

[0107] Example 1: Sericite forms a primary physical barrier, barium sulfate nanoparticles fill the gaps between the sheets, and hybrid materials further fill the nanoscale voids and bond with the resin matrix to form a three-dimensional multi-level filler barrier structure, which significantly improves the early water resistance and long-term salt spray resistance of the coating film.

[0108] Resin formulation (Example 1 vs. Example 2): In Example 2, increasing the proportion of high molecular weight resin accelerated surface drying to 12 minutes, slightly reduced gloss (91 vs. 93), and slightly lower salt spray resistance (580 h) compared to Example 1. This indicates that an excessively high proportion of high molecular weight resin may slightly affect the crosslinking density.

[0109] Hybrid material dosage (Example 1 vs. 3): In Example 3, reducing the hybrid material dosage (2.5 parts BN vs. 4.2 parts) resulted in a decrease in hardness to H and salt spray resistance to 520h. This demonstrates that the hybrid material dosage has a direct impact on film reinforcement and corrosion resistance.

[0110] Potential catalyst dosage (Examples 1, 9, 10): As the catalyst dosage increases (1 part → 2 parts → 3 parts), the actual drying time decreases (2.5 h → 2.0 h → 1.5 h), but the activation period decreases (6.0 h → 5.0 h → 4.0 h). The dosage of 2 parts in Example 1 achieves the best balance between drying rate and activation period.

[0111] Single-component system (Examples 6 and 7): Under the condition of baking at 110°C for 20 min, the performance of the coating film reached more than 90% of that of the two-component system, proving that the latent catalyst is also applicable to the low-temperature curing system, achieving energy saving and consumption reduction.

[0112] In conclusion: The technical solution of this invention has a significant synergistic effect. The four inventive points—high and low molecular weight compound resin system, modified nano-hybrid materials, potential catalysts, and composite functional fillers—work together to construct a high-performance waterborne acrylic polyurethane topcoat system.

[0113] Each inventive point is irreplaceable. Comparative Examples 1-7 respectively verified that the absence of any key technical feature would lead to a significant decrease in one or more performance characteristics.

[0114] The best implementation method is Example 1. It exhibits the best overall performance in terms of fast drying (surface dry 15 min / complete dry 2.0 h), high gloss (93), high hardness (2H), excellent corrosion resistance (salt spray resistance 600 h) and long activation period (5.0 h), meeting the stringent requirements of high-end industrial coating.

[0115] The technical solution of this invention has broad applicability. Examples 1-10 demonstrate that, although the film performance fluctuates slightly under different formulation parameter adjustments, it is still superior to the comparative example, proving that the technical solution of this invention has good formulation tolerance and industrial applicability.

[0116] It should be understood that the above description is only a specific embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.

Claims

1. A water-based acrylic polyurethane topcoat, characterized in that, Includes component A and component B; Component A comprises the following components by mass parts: The mixture consists of 35-50 parts of high and low molecular weight compounded hydroxyl acrylic resin, 2-5 parts of modified nano-hybrid materials, 15-25 parts of composite functional filler, 1-3 parts of potential catalyst, 3-6 parts of additives, and 20-30 parts of deionized water. Component A also includes a neutralizing agent; Component B is a crosslinking agent; Component B is a hydrophilic modified isocyanate curing agent, which includes hexamethylene diisocyanate trimer or its derivatives; The high and low molecular weight compounded hydroxy acrylic resin includes high molecular weight hydroxy acrylic resin and low molecular weight hydroxy acrylic resin. The modified nano-hybrid material is a hybrid material formed by in-situ composite of nano-boron nitride modified with silane coupling agent and graphene oxide. The potential catalyst is a metal complex formed by pre-complexing a metal compound with a complexing agent; The high molecular weight hydroxyl acrylic resin has a number average molecular weight of 50,000-80,000, a glass transition temperature of 40-60℃, and a hydroxyl value of 30-60 mgKOH / g. The low molecular weight hydroxyl acrylic resin has a number average molecular weight of 2000-5000 and a hydroxyl value of 120-160 mgKOH / g; the mass ratio of the high molecular weight hydroxyl acrylic resin to the low molecular weight hydroxyl acrylic resin is (1-2):

1. The modified nano-hybrid material contains hexagonal boron nitride with a sheet diameter of 100-500 nm and a thickness of 10-50 nm. The graphene oxide has a sheet diameter of 1-5 μm and a carbon-to-oxygen ratio of (2-4):1; The mass ratio of the nano-boron nitride to graphene oxide is (5-10):1; The silane coupling agent includes γ-methacryloxypropyltrimethoxysilane; The metal compound in the potential catalyst includes one or more of organobismibium, organozinc, and organozirconium. The complexing agent includes one or more of acetylacetone, 2,2'-bipyridine, and ethylenediaminetetraacetic acid; The molar ratio of the metal compound to the complexing agent is 1:(1-3); The composite functional packing includes micron-sized sheet packing and submicron-sized spherical packing; The micron-sized sheet-like filler includes at least one of sericite, kaolin, or talc, with a particle size of 5-15 μm. The submicron-sized spherical packing is selected from nano-barium sulfate or precipitated barium sulfate, with a particle size of 0.1-1μm; the mass ratio of the micron-sized sheet packing to the submicron-sized spherical packing is (2-3):

1.

2. The waterborne acrylic polyurethane topcoat according to claim 1, characterized in that, The ratio of component A to component B satisfies the molar ratio of NCO:OH as (1.2-1.5):

1.

3. The waterborne acrylic polyurethane topcoat according to claim 1, characterized in that, The additives include at least one of wetting and dispersing agents, substrate wetting agents, defoamers, film-forming aids, and rheology modifiers; The neutralizing agent includes at least one of N,N-dimethylethanolamine, 2-amino-2-methyl-1-propanol, and triethylamine, used to adjust the pH of component A to 7.5-8.

5.

4. A method for preparing the waterborne acrylic polyurethane topcoat as described in any one of claims 1-3, characterized in that, Includes the following steps: Pre-dispersion of hybrid materials: The prescribed amount of graphene oxide is added to a portion of deionized water and subjected to a first ultrasonic dispersion treatment to obtain a graphene oxide dispersion; under stirring conditions, nano-boron nitride modified with a silane coupling agent is slowly added to the graphene oxide dispersion, and then subjected to a second ultrasonic dispersion treatment to obtain a uniform and stable modified nano-hybrid material slurry. Paint slurry grinding: Mix the high and low molecular weight compounded hydroxy acrylic resin, some additives, composite functional fillers and the remaining deionized water evenly, put them into a sand mill for grinding and dispersion until the slurry fineness is ≤20μm. Paint mixing: In the qualified ground paint slurry, under stirring conditions, slowly add the modified nano-hybrid material slurry, the formula amount of potential catalyst, the remaining additives, and the neutralizer to adjust the pH value to 7.5-8.5, and continue stirring until uniform; Filtration: The mixed paint material is filtered through a filter screen to obtain component A of the topcoat; Packaging: Package component A and component B separately.

5. An application of a water-based acrylic polyurethane topcoat, characterized in that, The application of the waterborne acrylic polyurethane topcoat according to any one of claims 1-3 or the waterborne acrylic polyurethane topcoat prepared according to the method of claim 4 in the coating of metal substrates, the application including surface protection and decoration of engineering machinery, rail transportation, steel structures or automotive parts.

Citation Information

Patent Citations

  • Water-based cooling and heat-dissipating coating based on nano carbon material and preparation method of coating

    CN110734694A

  • Clear coating composition and method for producing coated article

    CN118749017A